PENGARUH MINUMAN FUNGSIONAL MENGANDUNG TEPUNG KEDELAI KAYA ISOFLAVON DAN SERAT PANGAN LARUT TERHADAP KADAR TOTAL KOLESTEROL DAN TRIGLISERIDA SERUM TIKUS PERCOBAAN - Nirmagustina, Dwi Eva (Jurnal Teknologi & Industri Hasil Pertanian, 2007)
The objective of this research was to evaluate the effect of functional drink that containe soybean flour rich in isoflavone, soluble dietary fiber, and other ingredients on the level of total cholesterol, HDL, LDL, and trigliseride in rat blood serum.  The formulation of functional drink consisted of soybean flour rich in isoflavone (0,115 g), soluble dietary fiber (fibergum) (3 g), vitamine C (0,06 g); sucrosa (6,605 g); aspartam (0,02 g); and flavour (orange) (0,2 g) in 200 ml functional drink.  The total concentration of soybean flour rich in isoflavone, soluble dietary fiber (fibergum), and vitamine C was based on optimation of human need.  Whereas the concentration of sucrosa, aspartam, and flavour (orange) based on organoleptic evaluation.  The result showed that functional drink caused a decrease the level of total blood serum rat colesterol after 1 and 2 month.  The HDL level of serum rat fed with standard ransum contain cholesterol was lower than the rat fed with sandard ransum only after 1 and 2 month because this was probably due to regulation feedback colesterol making in heart by enzim reductase HMG CoA. The functional drink caused decrease HDL level after 2 month . The functional drink also caused decrease the level of LDL and trigliseride after 2 month Keyword: functional drink, soy flour, isoflavon, soluble fiber, cholesterol, triglyseride